Visual Perception as Environmental Social Perception in the Animated Music Video "Sabda Alam" - Winny Gunarti Widya Wardani; Syahid , Syahid; Taufiq Akbar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Animated music video does not only act as a spectacle, but it can function as an informative as well as persuasive media campaign. As a product of visual culture, animated music videos have the potential to build a visual perception of the topic presented. Visual culture has now become a daily part of human activity, because visual technology allows various information, meanings or pleasures needed by humans to be fulfilled instantly through audiovisual language. This study discusses the animated music video "Sabda Alam" by students of the Raden Umar Said Vocational High School, Kudus, Central Java, which campaigns for the protection of endemic birds in Indonesia. This animated music video is interesting to study because it conveys campaign messages indirectly through 2D animated visual narratives. This study uses a combination method to analyze the visual language that shapes the audience's perception. Qualitatively, the discussion uses a social perception approach to analyze the basics of perception formation. Meanwhile, quantitatively, a survey was conducted on 150 viewers randomly to find the elements of perception formed, based on the product position target segmentation guidelines. The results showed that this animated music video was able to form perception of message content, perception of animated visualization, perception of narrative, perceptions of music, perception of environmental knowledge, perception of  wildlife care, and perception of causal factors of endemic birds extinction. It is hoped that the results of this research can become an academic reference, especially in the field of visual communication design, and become an inspirational and communicative media campaign model in product design development in the creative industries sector. The results showed that this animated music video was able to form perception of message content, perception of animated visualization, perception of narrative, perceptions of music, perception of environmental knowledge, perception of  wildlife care, and perception of causal factors of endemic birds extinction. It is hoped that the results of this research can become an academic reference, especially in the field of visual communication design, and become an inspirational and communicative media campaign model in product design development in the creative industries sector.